Respiratory Support During Pulmonary Artery Thromboembolia (Review) - D. A. Ostapchenko; A. I. Gutnikov; D. V. Rubanova; A. A. Losev (Общая реаниматология, 2020)
Pulmonary artery thromboembolia (PATE) is not a clinical entity as such, but a complication of diﬀerent diseases and conditions leading to deep thrombosis in the low tension circulation system, right cardiac chambers or causing local thrombosis in the pulmonary artery system. PATE is characterized by complex pathogenesis of respiratory failure of varying severity, which makes it diﬃcult to choose a respiratory support technique.Purpose of the overview: to show advantages of diﬀerent respiratory support techniques and prospects of high-ﬂux oxygen therapy with regard to PATE pathophysiology.82 sources were selected based on the principle of combining clinical and experimental data from papers published over the recent 5 years and earlier that are still relevant for medical practice.The overview presents the structure of main causes and prevalence of PATE and considers thrombogenesis stages and predominant manifestations of respiratory failure during PATE occurring due to inconsistency between pulmonary ventilation and perfusion. Review discusses ﬁve methods of respiratory therapy in PATE patients: low-ﬂux and high-ﬂux oxygen therapy, non-invasive and invasive artiﬁcial lung ventilation, extracorporeal blood oxygenation. Finally, the paper shows the eﬃcacy and limitations of these methods.Conclusion. High-ﬂux oxygen therapy seems to be the most eﬀective and promising technique in PATE patients thanks to absence of adverse cardiohemodynamic consequences, subjective comfort for patients, and relation to minimal risks of secondary infectious complications.Nevertheless, the clinical experience accumulated is insuﬃcient to make an absolute choice of one particular technique for respiratory support during PATE. It is necessary to continue investigating the clinical eﬃcacy of high-ﬂux oxygen therapy in the speciﬁc population of patients who experienced PATE.